(untitled) (Biological Sciences - PJSIR, 2005)
Levels of cadmium, lead, zinc, copper and chromium were determined in the head, middle and tail regions of the silver cat fish (Chryssichthys nigrodigitatus). Water and sediments from three neighbouring man-made fresh water ponds were also analyzed using atomic absorption spectrophotometer. The mean concentration of these metals were found to be more in the soil, followed by the water and then the fish. The highest concentrations of zinc between 33.05- 33.19 mg/ml and 39.72-40.13 mg/g, were found in the water and soil, respectively. Chromium concentration in water and soil ranged from 0.220-0.254 mg/ml and 0.335-0.347 mg/g, respectively. In the fish parts, zinc and chromium were found to be more in the head with values ranging from 19.05-19.23 mg/g and 0.210-0.215 mg/g, respectively. Cadmium, copper and lead were found to be more in the middle region, having values ranging from 0.260-0.261 mg/g, 4.60-4.62 mg/g and 0.320-0.321 mg/g, respectively. All metals investigated were consistently low in the fish tail. There was no significant difference in the mean concentration of all the metals in the three ponds at p £ 0.05, while the distribution of the metals in the fish parts and between the fish and the water was significantly different at p £ 0.05.